Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae